PREPARATION AND EVALUATION OF CYCLODEXTRIN COMPLEXES OF ANTI-TUBERCULAR DRUG RIFAMPICIN FOR IMPROVED BIOAVAILABILITY - Prakash Rao, B.; Suresh, Sarasija; Sah, Suresh; C, Narendra; Angbo, Manuka (International Journal of Ayurveda and Pharma Research, 2015)
The aim of the study was to increase the aqueous solubility, dissolution rate, stability, in vitro anti-tubercular activity and bioavailability of rifampicin by the way of inclusion complexation. Methyl B-cyclodextrin in case of rifampicin were used. Based on phase solubility studies that stoichiometry of complex of with respect to B-cyclodextrin for rifampicin was found to be 1:1 molar ratio. Different methods of preparation such as kneading and common solvent were employed to prepare the complexes. Formation of complexes In case of rifampicin, interaction of 4-methyl piperazin-1-ylimino-methyl (side chain) of rifampicin with the cyclodextrin molecule was confirmed by FTIR and 1H-NMR. The complexes prepared by different methods were subjected to solubility and in vitro dissolution studies. In case of rifampicin, in vitro anti-tubercular activity was found to be enhanced for the complexes of rifampicin indicated by a reduction in MIC of rifampicin. The oral bioavailability of rifampicin-MB-CD complex prepared by common solvent method was improved significantly. The results of stability studies revealed that stability of the drugs in solution and solid state were improved significantly due to complexation. Photostability of rifampicin is enhanced significantly by the way of complexation. Thus inclusion complexation of rifampicin with B-cyclodextrin, B-cyclodextrin derivatives and y-cyclodextrin improved its physical properties, bioavailability and in vitro activity.